BAHASA PRASANGKA SOSIAL DALAM CERPEN “CLARA” KARYA SENO GUMIRA AJIDARMA - A. Yusdianti Tenriawali (Kantor Bahasa Provinsi Maluku Utara, 2019)
This study discusses social prejudice language in short story “Clara” by Seno Gumira Ajidarma. Prejudiced language is also found in literary works. Literary works as imaginary works usually offer human and humanity, life and life problems. The author lived up to these issues with a sincerity which was then expressed back through the means of fiction by his views. Fiction tells the various problems of human life and its interaction with the environment and neighbor. Fiction is the result of contemplation, the author's reaction and environment and life. The purpose of this study is to identify language strategies that contain prejudices in short story “Clara” by Seno Gumira Ajidarma. This research is qualitative descriptive research. The data in this study is the text taken from short story “Clara atawa Wanita yang Diperkosa” by Seno Gumira Ajidarma. Data analysis in this study consist of (1) data collection in the form of text which is considered to show prejudice from short stories, and (2) texts odentification that have been obtained based on the expression of prejudices and rhetorical devices. The results showed that the literary language in the short story could not be separated from prejudice. Type of language strategies used are; repetition, generalization, and the appointment of minorities. It also shows that based on the data, all types of language strategies, repetition, generalization, minority appointments, and the name of origin tend to be used to denote negative prejudices.